Treatment of Early Hip Osteoarthritis: Ultrasound-Guided Platelet Rich Plasma versus Hyaluronic Acid Injections in a Randomized Clinical Trial - Doria, Carlo; Mosele, Giulia Raffaella; Caggiari, Gianfilippo; Puddu, Leonardo; Ciurlia, Emanuele (Joints, 2017)
Purpose The aim of this study was to compare the clinical efficacy of ultrasound-guided intra-articular injections of autologous platelet rich plasma (PRP) versus hyaluronic acid (HA) for symptomatic early osteoarthritis (OA) of the hip.Methods A prospective controlled double-blinded randomized trial on 80 patients with hip OA was conducted. The patients were divided in two groups of 40 patients each: group 1 underwent three PRP intra-articular ultrasound-guided injections, whereas group 2 underwent three HA injections. WOMAC, VAS, and Harris Hip Score were evaluated for both groups before and at 6 and 12 months after treatment.Results The two groups were comparable in age, sex, body mass index, and severity of hip OA. Both groups showed a significant improvement from baseline at 6-month and 12-month follow-ups for all the outcome measures. No major complications were observed during the treatment and at follow-ups in both the groups.Conclusion PRP did not offer significantly better results compared with HA in patients with moderate signs of OA, and thus it should not be considered as first-line treatment.Level of Evidence Level II, randomized controlled trial.
Keywords: hip; osteoarthritis; hyaluronic acid; platelet rich plasma; ultrasound; injection